Preliminary study on prevalence of larvae of Anisakidae family in European sea bass (Dicentrarchus labrax) - C.E.M. Bernardi (Food Control, 2009)
A total of 561 fresh European sea bass from North-East Atlantic ocean (F.A.O. zone 27) were examined for Anisakidae larvae detection. It is the first record on the prevalence of Anisakidae larvae in this fish specie. An unexpected high prevalence was found. The prevalence range was between 65 and 85%, in relation with the body weight of the subject. The results have an important consequence on epidemiology of anisakidosis and public health risk assessment.